Cluster randomised controlled trial of a financial incentive for mothers to improve breast feeding in areas with low breastfeeding rates: the NOSH study protocol. Issue 4 (11th April 2016) - Relton, Clare; Strong, Mark; Renfrew, Mary J; Thomas, Kate; Burrows, Julia; Whelan, Barbara; Whitford, Heather M; Scott, Elaine; Fox-Rushby, Julia; Anoyke, Nana; Sanghera, Sabina; Johnson, Maxine; et al.
Abstract : Introduction: Breast feeding can promote positive long-term and short-term health outcomes in infant and mother. The UK has one of the lowest breastfeeding rates (duration and exclusivity) in the world, resulting in preventable morbidities and associated healthcare costs. Breastfeeding rates are also socially patterned, thereby potentially contributing to health inequalities. Financial incentives have been shown to have a positive effect on health behaviours in previously published studies. Methods and analysis: Based on data from earlier development and feasibility stages, a cluster (electoral ward) randomised trial with mixed-method process and content evaluation was designed. The 'Nourishing Start for Health' (NOSH) intervention comprises a financial incentive programme of up to 6 months duration, delivered by front-line healthcare professionals, in addition to existing breastfeeding support. The intervention aims to increase the prevalence and duration of breast feeding in wards with low breastfeeding rates. The comparator is usual care (no offer of NOSH intervention). Routine data on breastfeeding rates at 6–8 weeks will be collected for 92 clusters (electoral wards) on an estimated 10 833 births. This sample is calculated to provide 80% power in determining a 4% point difference in breastfeeding rates between groups. Content and process evaluation will include interviews with mothers, healthcare providers, funders and commissioners of infant feeding services. The economic analyses, using a healthcare provider's perspective, will be twofold, including a within-trial cost-effectiveness analysis and beyond-trial modelling of longer term expectations for cost-effectiveness. Results of economic analyses will be expressed as cost per percentage point change in cluster level in breastfeeding rates between trial arms. In addition, we will present difference in resource use impacts for a range of acute conditions in babies aged 0–6 months. Ethics and dissemination: Participating organisations Research and Governance departments approved the study. Results will be published in peer-reviewed journals and at conference presentations. Trial registration number: ISRCTN44898617; Pre-results.